PENGARUH PENATAUSAHAAN BARANG MILIK DAERAH TERHADAP KUALITAS LAPORAN KEUANGAN PADA PEMERINTAH DAERAH KABUPATEN MUSI BANYUASIN (Studi Kasus Pada Sekretariat DPRD Kabupaten Musi Banyuasin) - Ahmad Irfansyah; Jumania Septariani (Sekolah Tinggi Ilmu Ekonomi Rahmaniyah Sekayu, 2022)
This study aims to determine the effect of Regional Property Administration on the Quality of Financial Reports of the Secretariat of DPRD Musi Banyuasin Regency. Data collection techniques used in this study were questionnaires. The population of this research was the secretariat employees of DPRD Musi Banyuasin Regency, the sample used were 30 respondents using purposive sampling method. This research was a quantitative research with simple linear regression analysis. The administration of regional property on the quality of financial reports was tested using hypothesis testing, namely the correlation test, the coefficient of determination and the partial test using SPSS software. Before testing the hypothesis, the data was first tested using the data quality test. The results showed that the coefficient of determination obtained was 90.2%, the variation in the Quality of Regional Apparatus Financial Reports variables could be explained by the Regional Property Administration variable, while the remaining 9.8% was explained by other variables not analyzed in this study. The test results partially show that the Administration of Regional Property has a significant effect on the Quality of Regional Financial Reports.